Effect of the stabilizers on properties of natural rubber latex - Sharmini A/P Joseph Pereira (School of Polymer Engineering, University Malaysia Perlis, 2016)
The effect of the stabilizers on properties of natural rubber latexwas investigated. Different stabilizer with different amount of the concentration was used to investigate the colloidal stability of the natural rubberlatex film. The mechanical stability, viscosity and mechanical properties of the Natural Rubber Latex are investigated using different types and concentration of stabilizers at different maturation time. The NRL films undergoes material characterization and compounding. Then, each of the different formulation undergoes pre-vulcanization process in water bath. The, the latex compound undergoes maturation and casting methods. Casting was carried out using glass plate. Then, the latex film in the liquid form allowed to dry and vulcanization process is carried out. Then the leaching process was carry out to make differentiate between the natural rubber latex that undergoes leaching and without the leaching process for the mechanical and physical properties. Then, each of the natural rubber latex film cut according to the specific dimension provided for each of the testing. For example, tensile test, swelling test and leaching test. Each of the test, the properties compared based on the different concentration of the stabilizer and different types of the stabilizer. For this experiment, we can identified the suitable concentration of stabilizer and the best stabilizer that can be used for the latex formulation to make film latex to maintain the colloidal stability of the natural rubber latex.